ANALISIS SISTEM DISTRIBUSI AIR BERSIH DI DESA KINIPAN KECAMATAN BATANG KAWA KABUPATEN LAMANDAU (Analysis Of Clean Water Distribution System In Kinipan Village, Batang Kawa District, Lamandau Regency) - Yosevina Yosevina; Resiana Herda (Fakultas Teknik Universitas Kristen Palangka Raya, 2021)
Water has an important role in the life of humans and other creatures in nature. There is no life in this world that does not need water. Water is essential for human consumption and has become one of the most important wealth. Population growth must be followed by the availability of healthy and sufficient clean water. The water can come from above ground level, below or from ground water (eg river water, lake water and so on) which must be treated before being used. The Batang Kawa River is the source of raw water for the residents of the Kinipan village and the planning for the construction of this simple processing unit is so that it can meet the raw water for the residents of the Kinipan village and pay attention to a good distribution system so that the distribution of clean water can fully become an important reference. Keywords: Clean Water, Clean Water Needs